Computational Prediction of Electronic and Photovoltaic Properties of Anthracene-Based Organic Dyes for Dye-Sensitized Solar Cells - Hongbo Wang; Qian Liu; Dejiang Liu; Runzhou Su; Jinglin Liu; Yuanzuo Li (International Journal of Photoenergy)
Three kinds of anthracene-based organic dyes for dye-sensitized solar cells (DSSCs) were studied, and their structures are based on a push–pull framework with anthracenyl diphenylamine as the donor connected to a carboxyphenyl or carboxyphenyl-bromothiazole (BTZ) as the acceptor via an acetylene bridge. The photoelectric properties of the three dyes were investigated using density functional theory (DFT). The simulations indicate that the improvement of anthracene-based dyes (the addition of BTZ and the change of alkyl groups to alkoxy chains) can reduce the energy gap and produce a red shift. This structural modification also improves the light capturing and the electron injection capability, making it excellent in photoelectric conversion efficiency (PCE). In addition, twelve molecules have been designed to regulate photovoltaic performance.